Osteoporosis Syndrome in Thalassaemia Major: An Overview - Meropi Toumba; Nicos Skordis (Journal of Osteoporosis)
Osteoporosis in thalassaemia major (TM) represents a prominent cause of morbidity. The mechanism of pathogenesis of bone disease (BD) in TM is multifactorial and complicated. Peak bone mass is achieved shortly after completion of puberty and normally remains stable until the third decade of life when age-related bone mass begins. Growth hormone (GH) and sex steroids play a crucial role in bone remodeling and in the maintenance of skeletal architecture during adult life. GH and insulin growth factors (IGFs) have anabolic effect in bone formation. Sex steroids act probably by increasing the expression of RANKL by osteoblastic cells and alterations in the RANK/RANKL/OPG system in favor of osteoclasts. Impaired GH secretion and lack of sex steroids in thalassemic patients due to pituitary damage, contribute to failure of achieving optimal peak bone mass. Other endocrine complications such as hypoparathyroidism and vitamin D deficiency have also a detrimental role on bones in TM. It is still questionable whether the international criteria for defining osteopenia and osteoporosis are relevant to patients with TM; also a question arises for the diagnostic methods such as DEXA scan and management of osteoporosis with known treatment protocols, in the thalassaemic patient.